ASSESMENT OF THE INJURY SEVERITY OF THE PEDESTRIAN LOWER LIMBS AT THE COLLISION WITH A VEHICLE - TOLEA Bogdan; ANTONYA Csaba; BELES Horia (Annals of the Oradea University: Fascicle Management and Technological Engineering, 2015)
—The purpose of the paper is to determine the severity of the injury that may appear at the collision of the frontal part of a vehicle with the pedestrian’s lower limbs. In this study, the bio-mechanic model of the lower limbs was constructed, in order to determine the bending moment of the tibia. The collision forces that were used as input data were collected from a simulation performed in a traffic accident reconstruction software. The developed multi-body simulation is considering all forces acting on the lower limb. The injury severity is estimated using the bending moment of the tibia.